ANALISIS KINERJA STAFF BANQUET SECTION DAN PENGARUHNYA TERHADAP KUALITAS PELAYANAN DI HOTEL SWISS BELL MALEOSAN MANADO - Jelly Sendow (UPT Penelitian Sekolah Tinggi Ilmu Pariwisata Manado, 2022)
The purpose of this study was to analyze, quantify and explain the performance effects section banquet staff to service quality in hotels swiss bell Maleosan Manado. This study used observational techniques, surveys and interviews. Method of sampling taken at random or random. The final results of this study as a simple linear regression analysis calculations derived equations After doing research we obtained a simple linear regression analysis with the equation Y = 50 + 0.3 X which shows that each time increment the unit variable X Performance Staff Banquet Section will cause the increase in variable Y Quality Service with a value of 50. For the determinant coefficient r2 = 0.36 or 36%. This suggests that the increase in variable service quality caused by Section Banquet Staff Performance is 36%. While 64% are caused by other factors not studied by researchers such as equipment, lack of effective service systems and the unavailability of food menu. Hotel Management Swiss Bell Hotel Maleosan Manado must continue to improve the performance of both the guests to be positive as the above assessments can continue to survive and even grow.